Elevated Tacrolimus Levels at Time of Diagnosis of COVID-19 Compared to Baseline Among Hospitalized Organ Transplant Recipients. Issue 11 (November 2022) - Mecadon, Krista; Hardesty, Anna; Vieira, Kendra; Rogers, Ralph; Merhi, Basma; Osband, Adena J.; Bayliss, MD, George; Gohh, Reginald; Morrissey, Paul; Farmakiotis, Dimitrios
Background: The effect of COVID-19 on immunosuppressant drug levels in organ transplant recipients (OTRs) has not been adequately studied. Objective: To study the effect of COVID-19 on tacrolimus trough levels (primary outcome) in OTRs and the association of the later with acute kidney injury, bacterial infection, and oxygen requirements. Methods: We studied adult (>18-year-old) hospitalized OTRs with COVID-19, who were receiving tacrolimus between 3/1 and 12/16/2020. Results: Among 30 OTRs, 67% were men, 90% had a kidney transplant. Median age was 60.5 (interquartile range [IQR]: 45-68) years, median time from transplant 36 (IQR: 20-84) months. Tacrolimus troughs were higher on admission for COVID-19 than baseline (average over 6 months prior) ( P = .001). Eighteen patients (60%) had admission tacrolimus trough >10, 5 (17%) >20 ng/mL. Patients with diarrhea had borderline higher tacrolimus troughs, compared to those without diarrhea ( P = .09). Organ transplant recipients with a tacrolimus trough >10 ng/mL were more likely to have elevated aspartate aminotransferase on admission ( P = .01) and require supplemental oxygen. ( P = .026). Conclusion and Relevance: Tacrolimus trough levels were elevated in most OTRs with COVID-19 at the time of hospital admission, compared to baseline. Potential mechanisms are diarrhea and hepatic involvement in COVID-19. In OTRs with COVID-19, including outpatients, immunosuppressant drug levels should be closely followed; management of immunosuppression should be individualized.